A educação socioambiental nos cursos de formação de engenheiros da UFMS - Quevedo, Valeria Ramos Baltazar (2022)
It sought to investigate the existence of elements of education, socio-environmental education, and sustainability, as well as their aspects, in engineering courses at the Federal University of Mato Grosso do Sul (UFMS) to present a proposal for the insertion of the socio-environmental education thesis. in engineering professional training, consistent with environmental education policies and national engineering curriculum guidelines. The defense is that the orientation of a curriculum that allows the production and dissemination of knowledge, contextualized with socio-environmental education is strategic for engineers prepared to deal with socio-environmental issues. A socio-environmental education was chosen to provide training for engineers, promoting an ethical and responsible posture, taking into account the social and environmental impacts that their decisions can also entail. To support the research, a historical review of the formation of engineering courses, legislation, guidelines, and theoretical contributions of environmental education was carried out. Documentary analysis was used to obtain the elements investigated, with interdisciplinarity and transversality being the indicators for the analysis, and the views of nature used as parameters to define the aspects that prevail in the documents. Using the theory of representations, through mental maps, with a focus on the civil engineering course, the perception of the construction of environmental knowledge that occurs during graduation was obtained. The results showed that within the UFMS, existing actions are aimed at sustainable development, with a prevailing focus on management, physical space, activities and specific interventions, contextualizing environmental education and graduation mainly through extension actions. In the graduations, the absence of theoretical and methodological support, as well as the differences in the approach to the theme, demonstrate that environmental education is not an integrating unit. Regarding the perception of the environment, the results indicate that there are no significant changes between freshmen and graduates of the course, for most academics the human being is not seen as part of the environment, evidencing the absence or failure of environmental education. These analyzes represent the need for interventions in the approach to environmental education in engineering. In this way, it is suggested that the bases of environmental knowledge should be included in the subjects with basic mandatory content common to all engineering qualifications, homogenizing environmental knowledge to academics. This knowledge should provide a basic theoretical and epistemological contribution and be deepened during the course in the subjects inherent to each engineering emphasis. Finally, extension is suggested as a field to make an analogy between learning theoretically systematized knowledge and real-life issues, contextualized with the environmental issue, providing the academic performance within their area of knowledge and dialogue with society.